Ecological niche of Neanderthals from Spy Cave revealed by nitrogen isotopes of individual amino acids in collagen. Issue 93 (April 2016) - Naito, Yuichi I.; Chikaraishi, Yoshito; Drucker, Dorothée G.; Ohkouchi, Naohiko; Semal, Patrick; Wißing, Christoph; Bocherens, Hervé
Abstract: This study provides a refined view on the diet and ecological niche of Neanderthals. The traditional view is that Neanderthals obtained most of their dietary protein from terrestrial animals, especially from large herbivores that roamed the open landscapes. Evidence based on the conventional carbon and nitrogen isotopic composition of bulk collagen has supported this view, although recent findings based on plant remains in the tooth calculus, microwear analyses, and small game and marine animal remains from archaeological sites have raised some questions regarding this assumption. However, the lack of a protein source other than meat in the Neanderthal diet may be due to methodological difficulties in defining the isotopic composition of plants. Based on the nitrogen isotopic composition of glutamic acid and phenylalanine in collagen for Neanderthals from Spy Cave (Belgium), we show that i) there was an inter-individual dietary heterogeneity even within one archaeological site that has not been evident in bulk collagen isotopic compositions, ii) they occupied an ecological niche different from those of hyenas, and iii) they could rely on plants for up to ∼20% of their protein source. These results are consistent with the evidence found of plant consumption by the Spy Neanderthals, suggesting a broader subsistence strategy than previously considered.